PENGARUH SISTEM PEMBERIAN KREDIT KUPEDES TERHADAP TINGKAT NON PERFORMING LOAN (NPL) (STUDI PADA PT. BRI UNIT UJUNG BATU II CABANG UJUNGBATU) - Makmur, Indra Wahyu Prasetiyo, Andi Afrizal, (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2017)
This research is purpose to determine the system of crediting KVP EDES on BRI Ujung Batu II Branch Ujung Batu, knowing the level of NP L in BRI Unit Ujung Batu II Branch Ujung Batu, and determine the influence the system of credit KUPEDES the level of NP L in the BRI Unit Ujung Batu II Branch Edge Stone. This research was conducted in BRI Unit Ujung Batu 11 This type of research is associative research, the research purpose to determine the relationship between two or more variables, which is expected to be constructed a theory that could serve to explain, predict, and control a symptom. Data obtained in the formof primary data and secondary data obtained from questionnaires.Data analysis technique used is the classical assumption test consisting of (1) test for normality, (2) test multikolonearitas, (3) heteroscedasticity test and (4) autocorrelation test and test hypotheses consisting of (1) test the coefficient of determination and (2) statistical test. Based on the analysis of the test can be concluded that: Lending System KUPEDES simultaneously affect the level of NPL BRI Ujung Batu 11 Directly affect thevariables X and Y. Based on the descriptive analysis concluded that the system of credit has the effect of 5. 6% to the increase in NP L. The results of the study are the BRI Unit Ujung BatuII Should the marketing in order to further tighten and more thoroughly analyzing the business and the character of the debtor, in order to know exactly the ability to pay and the designation of the loan capital in order to really credit KVP EDES used forbusiness purposes. It can be concluded that the system of distribution KVP EDES has an influence on the levelof NPL.